Friends or just fans? Parasocial relationships in online television fiction communities - Charo Lacalle; Beatriz Gómez-Morales; Sara Narvaiza (Communication & Society (Formerly Comunicación y Sociedad), 2021)
This paper explores parasocial phenomena on social media pages related to Spanish television fiction by analysing the development of parasociality through relationships established between users and characters and the characteristics of this type of online community. The sample consisted of 4,762 spontaneous comments posted on social media pages (1,598 on Facebook and 3,164 on Twitter) linked to television series. Comments published between 1 January 2018 and 31 May 2020 were compiled the day after the premiere of each fiction. Our findings confirm those of previous researchs on the similarity between parasocial relationships with fictional characters and relationships in real life. This study also substantiates that women’s comments show a greater tendency to draw associations between parasocial relationships and daily life. We also find a link between programme longevity and audience success on the one hand, and the intensity of parasocial relationships with the characters on the other. The relationships among community members reveal a degree of narcissism, prompting more self-disclosure than interaction with the rest of the users. Therefore, such relationships are closer to consociality (Kozinets, 2015) than parasociality, although significant differences concerning gender identity are also found in this context.